Hubungan Bernyanyi Gaya Dendang Terhadap Popularitas Lagu “Bayang-Bayang Rindu” Ciptaan Edi Elmitos - Anggi Azhari Lubis; Yos Sudarman (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This research aims to determine the relationship between singing in the singing style and the popularity of the song